“Stopped in the middle” with Elm,arie Costandius: playing with interruptions/continuities - Romano, Nike Irene; Bozalek, Vivienne; Shefer, Tamara (Critical Studies in Teaching and Learning, 2025)
This paper is written in memory of our friend and colleague, Elmarie Costandius, a visual artist and academic, whose untimely and unexpected death deeply affected us. While we had worked with Elmarie in various research projects, short courses, and workshops, over a period of ten years or so, in this article we refer to a series of encounters, in which we came together to explore a decolonial and post qualitative inquiry practice as part of a South African Swedish Universities Forum (SASUF) project (2020 - 2022). Entitled (Re)configuring Scholarship in Higher Education, the project focused on alternative ways of doing pedagogies and inquiry in the current context of higher education precarities and the consequent imperative for transformation. We wanted to explore how feminist new materialist imaginaries could be put to work with affective embodied practices to expand our thinking and reconfigure our scholarship. Guided by Elmarie’s experimental arts-based approach, we opened ourselves to the affordances of playfulness, creative, serious and experimental thinking-making-doings, and the vulnerabilities of these embodied, relational scholarly praxes. Stopped in the middle, we show how our entangled thinking-making-doings continue Elmarie’s legacy.